“If I do not have any money, why do you want my inheritance?”: The Figure of the Beggar in the Poetry of Joaquín Pablo Posada (2020)
The popular figure of the beggar is characterized by his joy, comicalness and social self-exclusion. In the nineteenth century, a new approach, one of a realistic nature, emerged around this character. This paper aims to recover to critical attention the poetic work of the Colombian Joaquín Pablo Posada, practically forgotten these days, in order to examine how he shapes the figure of the beggar in a time of transition. The findings show the existence of a hybrid imaginary (halfway between the cultured and the popular) of a jocular-serious nature. On the one hand, traditional traits are maintained, which include the beggar within the festive tendency. On the other hand, a modern denunciation is introduced about the beggar’s physical and moral sufferings, which challenge the discourse of bourgeois elites, without forsaking its central scheme. In the paper’s conclusions, the complexity of Posada's character is compared to other poetic subjects constructed during the nineteenth and twentieth centuries, which usually adhere to a single face of this figure, either the traditional or modern trait.